1957
DOI: 10.1084/jem.106.6.835
|View full text |Cite
|
Sign up to set email alerts
|

Predetermination by Infection and by Vaccination of Antibody Response to Influenza Virus Vaccines

Abstract: The antibody orienting effects of prior infections with antigenic variants of influenza viruses were confirmed by studies with monovalent adjuvant vaccines and with polyvalent aqueous and adjuvant preparations. In either case, the predominant antibody response was of a "booster" type, directed against the major antigens of strains of original infection. It was shown that vaccination with appropriate strains, selected as antigenic prototypes, could orient or predetermine subsequent antibody response upon revacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

1959
1959
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 11 publications
3
59
0
Order By: Relevance
“…The Eskimos studied by Reinhard & Gerloff (1960) and Reinhard (1962) were probably less isolated than the inhabitants of Tristan da Cunha. The Tristan islanders of all ages apparently responded mainly to the viruses prevalent when the epidemics occurred on the island and this can be interpreted as a striking natural experiment in confirmation of the ideas of Davenport and his colleagues (Davenport & Hennessey, 1957). They believe that the broadness and altered specificity of the response of older subjects to vaccination with monospecific vaccines is due to their 'experience' of more and different influenza antigens and not to any hypothetical ageing process.…”
Section: Relation Between Blood Groups and Virus Infectionsupporting
confidence: 51%
“…The Eskimos studied by Reinhard & Gerloff (1960) and Reinhard (1962) were probably less isolated than the inhabitants of Tristan da Cunha. The Tristan islanders of all ages apparently responded mainly to the viruses prevalent when the epidemics occurred on the island and this can be interpreted as a striking natural experiment in confirmation of the ideas of Davenport and his colleagues (Davenport & Hennessey, 1957). They believe that the broadness and altered specificity of the response of older subjects to vaccination with monospecific vaccines is due to their 'experience' of more and different influenza antigens and not to any hypothetical ageing process.…”
Section: Relation Between Blood Groups and Virus Infectionsupporting
confidence: 51%
“…Influenza viruses of the HlNl type caused epidemic influenza in the decade 1947-1957, but had not been isolated from cases of human influenza since the appearance of the epidemic Asian H2N2 strains in 1957. The recent HlNl strains, characterised by the reference strain A/USSR/90/77, are related to the HlNl strains circulating from 1947-1957(WHO, 1978a, and are antigenically and genetically similar to a virus isolated in the United States in 1950 (Nakajima, Desselberger and Palese, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…A fourfold or greater antibody response to B/Kanagawa HA antigen was seen in only 3-50% of the students tested, and the geometric mean HI titres remained unchanged at approximately 50-70. DISCUSSION A programme of annual influenza immunization has been recommended and carried out in Japan since 1960 (Dowdle et al 1980). This assumes that the high incidence of influenza-associated morbidity among schoolchildren plays a role in extending outbreaks of influenza in the general population.…”
Section: Serodiagnosis Of Natural Infection With Influenza a Virus Dumentioning
confidence: 99%
“…However, in terms of cross-reactivity of the HI antibody acquired after repeated immunizations to the various antigenic drift strains, a difference was found between persons who had been naturally infected and persons who had only been exposed to HINI virus in the form of vaccine. Recent studies reported that following immunization with either inactivated whole or split vaccines, most adults responded mainly by producing a cross-reactive or common antibody among Hong Kong viruses (Webster et al 1976;Schild et al 1977;Oxford et al 1979), probably indicating original antigenic sin after vaccination with influenza viruses (Hennessy, Davenport & Francis, 1955; influenza (HJNJ) immunization in Japan Davenport & Hennessy, 1956, 1957. In the present studies, the poorer crossreactivity to some drift strains, including Hswl antigen, among the people who had not been infected may be explained by the lack of immunological memory to a cross-reactive antigenic determinant which the natural infection may induce but the artificial immunization may not.…”
Section: Serodiagnosis Of Natural Infection With Influenza a Virus Dumentioning
confidence: 99%
See 1 more Smart Citation